Analis Kesalahan Berbahasa dalam Komentar Pengguna Akun tiktok Vina Mulyana Kajian sosiolinguistik - Khairunnisa Purba; Yulia Arfianty (Ikatan Dai Indonesia, 2025)
The content available on the TikTok application is increasingly diverse from educational content, comedy, vlogs, to personal experiences of its users. On TikTok, the content is free to explore and can be used anytime and anywhere. As a result,